Temperature and thermal emission of cosmic dust in the vicinity of the Sun, Vega and Fomalhaut. - Myrvang, Margaretha; Baumann, Carsten; Mann, Ingrid; Stamm, Johann Immanuel (UiT The Arctic University of Norway, 2018)
Poster presentation